Failure to upregulate Agrp and Orexin in response to activity based anorexia in weight loss vulnerable rats characterized by passive stress coping and prenatal stress experience - Boersma, Gretha J. (Psychoneuroendocrinology, 2016)
We hypothesize that Anorexia Nervosa (AN) poses a physiological stress. Therefore, the way an individual copes with stress may affect AN vulnerability. Since prenatal stress (PNS) exposure alters stress responsivity in offspring this may increase their risk of developing AN. We tested this hypothesis using the activity based anorexia (ABA) rat model in control and PNS rats that were characterized by either proactive or passive stress-coping behavior. We found that PNS passively coping rats ate less and lost more weight during the ABA paradigm. Exposure to ABA resulted in higher baseline corticosterone and lower insulin levels in all groups. However, leptin levels were only decreased in rats with a proactive stress-coping style. Similarly, ghrelin levels were increased only in proactively coping ABA rats. Neuropeptide Y (Npy) expression was increased and proopiomelanocortin (Pomc) expression was decreased in all rats exposed to ABA. In contrast, agouti-related peptide (Agrp) and orexin (Hctr) expression were increased in all but the PNS passively coping ABA rats. Furthermore, DNA methylation of the orexin gene was increased after ABA in proactive coping rats and not in passive coping rats. Overall our study suggests that passive PNS rats have innate impairments in leptin and ghrelin in responses to starvation combined with prenatal stress associated impairments in Agrp and orexin expression in response to starvation. These impairments may underlie decreased food intake and associated heightened body weight loss during ABA in the passively coping PNS rats.